Main structural features of graphene materials controlling the transport properties of epoxy resin-based composites. (April 2018) - Sánchez-Hidalgo, R.; Yuste-Sanchez, V.; Verdejo, R.; Blanco, C.; Lopez-Manchado, M.A.; Menéndez, R.
Graphical abstract: Highlights: Optimal control of the structure and morphology of graphene materials. The dispersion of graphene in the epoxy resin is strongly dependent of the BET surface area. Custom-made graphene-based polymer nanocomposites. Thermal conductivity benefits from a high aromatic restoration. Electrical conductivity requires the right balance of filler/matrix interaction and aromatic restoration. Abstract: Graphene materials (GMs) are deeply studied as nanoreinforcements of polymer matrices, especially for epoxy matrices. Here, we analyze the effect of GMs on the transport properties of a poly(bisphenol A-co-epichlorohydrin) resin. In particular, we focus on the effect of the morphology, chemical composition and structure of different GMs obtained by varying the reduction temperature of the thermal/exfoliation treatment of graphite oxide synthesized by a modified Hummers method. The dispersion degree of the GMs was studied by microscopy techniques, showing a strong dependence on the specific surface area and chemical composition of the graphene material. The transport properties imposed different requirements on GMs. The thermal conductivity benefited from a high aromatic restoration. Meanwhile, the electrical conductivity required the right balance of filler/matrix interaction and aromatic restoration.